Newly Qualified Professional Nurses’ Readiness for the Independent Practice Role - Warriodene Hansen (Nursing Research and Practice)
ConclusionThe participants of this study all described that newly qualified professional nurses’ transition to nursing was challenging. The participants agreed that the transition to the professional role is a concern that needs to be addressed. This study found a need for professional support and guidance of newly qualified professional nurses within the clinical environment.